2001
DOI: 10.1055/s-2001-16896
|View full text |Cite
|
Sign up to set email alerts
|

Validität der Operationalisierten Psychodynamischen Diagnostik (OPD) bei familientherapeutisch behandelten Drogenabhängigen im adoleszenten und jungen Erwachsenenalter1

Abstract: The paper describes results of "operationalized psychodynamic diagnostics" (OPD) with 54 adolescent and young adult drug addicts prior to outpatient family therapy. Focus of investigation is the prognostic and factorial validity of the OPD-system. Furthermore, relationships between conflicts and psychic structure are investigated. The use of the OPD-system allows a clinical description of the patient sample. Thus, adolescent drug addicts are characterized by autonomy versus dependence and self-esteem conflicts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
3
0
10
Order By: Relevance
“…For example, patients with a lower level of structural integration have a more negative body concept (G. Schneider et al, 2008), show more insecure attachment styles (Schauenburg, 2000), treat themselves and others in a more hostile way (Mestel et al, 2004), are prone to self-injurious behavior (Böker et al, 2008;Spitzer et al, 2002a), are more likely to experience psychotic symptoms (Uzdawinis et al, 2010), have a longer duration of mental illness (Rudolf et al, 1996), and tend to be indicated for psychiatric rather than psychotherapeutic treatment (G. . Moreover, there is some evidence that a better level of structural integration is advantageous in terms of symptom change or treatment success, as judged by patients or therapists (Müller et al, 2006;Rudolf et al, 1996;Spitzer et al, 2004;Strauß et al, 1997; but also see Thomasius et al, 2001).…”
Section: Reliabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…For example, patients with a lower level of structural integration have a more negative body concept (G. Schneider et al, 2008), show more insecure attachment styles (Schauenburg, 2000), treat themselves and others in a more hostile way (Mestel et al, 2004), are prone to self-injurious behavior (Böker et al, 2008;Spitzer et al, 2002a), are more likely to experience psychotic symptoms (Uzdawinis et al, 2010), have a longer duration of mental illness (Rudolf et al, 1996), and tend to be indicated for psychiatric rather than psychotherapeutic treatment (G. . Moreover, there is some evidence that a better level of structural integration is advantageous in terms of symptom change or treatment success, as judged by patients or therapists (Müller et al, 2006;Rudolf et al, 1996;Spitzer et al, 2004;Strauß et al, 1997; but also see Thomasius et al, 2001).…”
Section: Reliabilitymentioning
confidence: 96%
“…Schneider, Lange, & Heuft, 2002;G. Schneider, Mendler, Heuft, & Burgmer, 2008;Spitzer, Michels-Lucht, Siebel, & Freyberger, 2002a, 2002b, 2004Schauenburg, 2000;Strauß, Hüttmann, & Schulz, 1997;Thomasius et al, 2001;Uzdawinis et al, 2010). In the following, we highlight the most relevant findings.…”
Section: Reliabilityunclassified
“…Eine Studie [6] fand keine bedeutsamen Unterschiede hinsichtlich Geschlecht, Familienstand, Ausbildung und beruflicher Stellung zwischen den jeweiligen strukturellen Integrationsstufen. Keine Assoziation zwischen Alter und Strukturniveau berichtete eine andere Untersuchung [9]. Mit Blick auf die klinischen Diagnosen sind die Ergebnisse weniger einheitlich: In zwei Studien [4, 6] lieûen die symptombezogenen ICD-10-Diagnosen keinen Rückschluss auf das Strukturniveau zu; kritisch ist allerdings einzuwenden, dass ein Ansatz [4] die Persönlichkeitsstörungsdiagnosen nicht berücksichtigte.…”
Section: Introductionunclassified
“…Der dritte Faktor " K ö rper " fasst vor allem die k ö rperbezogenen Items, wie etwa die Darstellung vorwiegend somatischer Beschwerden und die Motivation zu einer somatischen Therapie zusammen. Zu einem vergleichbaren Ergebnis kam eine Untersuchung, welche ebenfalls 3 Faktoren bei einer Varianzaufkl ä -rung von 77 % identifi zierte (Faktoren: " Somatik " , " Psychotherapiemotivation und g ü nstige Voraussetzungen " , " Sensibilit ä t f ü r psychische Belastung " ) [16] . Schlie ß lich wurde eine L ö sung mit 5 Faktoren und einer Varianzaufkl ä rung von 68 % ermittelt (Faktoren: " Somatik " , " Psyche " , " Einsichtsf ä higkeit " , " Ressourcen " , " Compliance " ) [17] .…”
Section: Die Operationalisierte Psychodynamische Diagnostik (Opd-2): unclassified